Prurigo Pigmentosa: A Clinicopathological Report of Three Middle Eastern Patients - N. Almaani; A. H. Al-Tarawneh; H. Msallam (Case Reports in Dermatological Medicine)
Prurigo pigmentosa is a unique cutaneous inflammatory disorder characterized by a sudden onset of pruritic and erythematous macules, urticarial papules, and plaques that may coalesce to form a reticulated pattern. Lesions typically heal within weeks leaving a reticulated and mottled postinflammatory hyperpigmentation. The majority of reported cases originate from Japan with much fewer cases described worldwide without predominant ethnicity. The histopathological features of prurigo pigmentosa can be nonspecific; however, distinct features exist for each stage of the disease. The aetiology of prurigo pigmentosa is not fully understood. However, ketoacidosis has been implicated in the pathogenesis and indeed prurigo pigmentosa has been associated with ketoacidotic states such as diabetes mellitus, fasting, dieting, and anorexia nervosa. In this report, we present 3 Jordanian patients with prurigo pigmentosa and describe their clinicopathological features. One patient developed prurigo pigmentosa while fasting during the month of Ramadan and another was undertaking a strict diet. No associations were identified in the third patient. In view of the largely nonspecific clinical and histological features, a high index of suspicion is required as many cases of prurigo pigmentosa are probably undiagnosed.